Intimate Partner Abuse Among Rohingya Women and Its Relationship With Their Abilities to Reject Husbands’ Advances to Unwanted Sex - Islam, M Mofizul (Journal of interpersonal violence, 2022)
Currently, around a million Rohingya refugees live in Cox?s Bazar, Bangladesh. Displacement from homelands and restrictions on movement in the refugee camps may exacerbate intimate partner abuse (IPA) against refugee women and their abilities to reject husbands? advances to unwanted sex. This study examines Rohingya refugee women?s attitudes toward and experience of intimate partner abuse (IPA) and their impact on the abilities to reject husbands? advances to unwanted sex. A survey was conducted among Rohingya refugee women in Cox?s Bazar, Bangladesh. Women?s attitudes toward IPA, and experience of IPA were the exposure variables. Women?s abilities to say ?no? to husbands? advances to unwanted sexual intercourse was the outcome variable. Multivariable logistic regression models were used to examine the relationships. Participants? median age was 22 years (range: 13-41). Most women perceived hitting/beatings by their husbands in certain situations as justifiable, 72% had experienced such abuse and 56.5% had to engage in unwanted sexual intercourse with their husbands. Women with increasing leniency towards hitting/beatings and those who had experienced such abuse were less likely to be able to say ?no? to husbands? advances to unwanted sexual intercourse. Rohingya women?s attitudes toward and experience of IPA are associated with their abilities to say ?no? to husbands? advances to unwanted sex. Intervention is needed to denormalize the current practice of IPA, create awareness against IPA, and ensure formal education for girls.